2013
DOI: 10.1017/s0007123413000124
|View full text |Cite
|
Sign up to set email alerts
|

Gaming Democracy: Elite Dominance during Transition and the Prospects for Redistribution

Abstract: Inequality and democracy are far more compatible empirically than social conflict theory predicts. This article speaks to this puzzle, identifying the scope conditions under which democratization induces greater redistribution. Because autocrats sometimes have incentives to expropriate economic elites, who lack reliable institutions to protect their rights, elites may prefer democracy to autocratic rule if they can impose roadblocks to redistribution under democracyex ante. Using global panel data (1972–2008),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(55 citation statements)
references
References 43 publications
(16 reference statements)
1
52
0
2
Order By: Relevance
“…PDI-P, the main opposition party, obtained the 4 To the best of our knowledge, there are only two other papers that have empirically documented the impact of nondemocratic legacies on governance outcomes. Albertus and Menaldo (2014) showed that income redistribution is lower in democracies that are preceded by democratic transitions where nondemocratic elites remained powerful-for example, in transitions where the new democracy adopted the constitution of the previous regime. Martinez-Bravo (2014) showed that the village-level appointees that a new democracy inherits from the previous regime have strong incentives to engage in electoral malpractice for strategic reasons.…”
Section: National-level Political Contextmentioning
confidence: 99%
“…PDI-P, the main opposition party, obtained the 4 To the best of our knowledge, there are only two other papers that have empirically documented the impact of nondemocratic legacies on governance outcomes. Albertus and Menaldo (2014) showed that income redistribution is lower in democracies that are preceded by democratic transitions where nondemocratic elites remained powerful-for example, in transitions where the new democracy adopted the constitution of the previous regime. Martinez-Bravo (2014) showed that the village-level appointees that a new democracy inherits from the previous regime have strong incentives to engage in electoral malpractice for strategic reasons.…”
Section: National-level Political Contextmentioning
confidence: 99%
“…Similar to the common identification of autocratic systems with inequality, Albertus and Menaldo (2014) found that economic elites impede the redistribution of resources, even during democratic regimes. Using a global, panel data set, spanning the years 1972-2008, they found that democratic regimes are better able to avoid the trap of elite dominance by crafting a new constitution protected from the prejudices of the outgoing regime.…”
Section: Neocolonial Theory Of Localizationmentioning
confidence: 57%
“…Constitutions under democracy that are inherited from dictatorship shape the rules of the political game in such a way that rightwing parties are likely to be more represented, the political system is more prone to gridlock, the military is more powerful, and local governments lack autonomy. The veracity of these mechanisms in protecting outgoing dictators from punishment echoes the findings in Albertus and Menaldo (2013), who demonstrate their broader impact for the economic interests of elites beyond simply avoiding punishment.…”
mentioning
confidence: 59%